Effects of Temperature and Salinity on the Growth, Reproduction, and Carotenoid Accumulation in Artemia sinica and Transcriptome Analysis - Yucai Xue; Gang Jiang; Huang Shu; Weilong Wang; Xuxiong Huang (Fishes)
Brine shrimp (Artemia), rich in carotenoids, are widely used in intensive aquaculture to supplement nutrients and enhance the coloration of farmed organisms. This study investigates the growth, reproduction, and carotenoid accumulation in Artemia sinica under varying salinity and temperature conditions. The results showed that temperature and salinity displayed significant interactions with survival, body length, and carotenoid accumulation in the body. The optimal survival and growth conditions of A. sinica (Bohai Sea Gulf) were a temperature range of 25–30 °C and a salinity range of 30–50‰. High temperatures accelerated growth and sexual maturity at the expense of survival rates, while temperatures below 20 °C prevented ovigerous development. Extreme salinity levels negatively affected survival and growth, though high salinity promoted sexual maturity. Carotenoids in A. sinica mainly accumulate as echinenone and canthaxanthin form. Carotenoid accumulation decreased with increased temperature and salinity, and the temperature effect decreased with rising salinity. A. sinica cultivated at a salinity of 10‰ and a temperature of 25 °C exhibits the highest carotenoid content. Transcriptomic analysis revealed that high temperatures primarily affected genes related to stress response and metabolism, while high-salinity regulated genes associated with ion balance and signaling pathways. These findings provide a theoretical basis for enhancing Artemia sinica aquaculture and optimizing cultivation conditions, offering novel insights into nutritional and environmental impacts on brine shrimp biology.